Does Alcohol Hangover Affect Emotion Regulation Capacity? Evidence From a Naturalistic Cross-Over Study Design. (12th November 2020) - Gunn, Craig; Fairchild, Graeme; Verster, Joris C; Adams, Sally
Abstract: Aims: The aim of this study was to investigate the effects of alcohol hangover on emotion regulation. Methods: Forty-five non-smoking, healthy participants aged between 18 and 30 years completed a lab-based emotion regulation task assessing cognitive reappraisal and an emotion regulation questionnaire (State-Difficulties in Emotion Regulation Scale [S-DERS]) when hungover (morning following a night of heavy drinking) and under a no-hangover condition in a naturalistic, within-subjects design study. Results: Participants reported poorer emotion regulation overall ( P < 0.001, d = 0.75), and for the subscales 'Non-Acceptance', 'Modulation' and 'Clarity' ( P s ≤ 0.001, ds ≥ 0.62), but not 'Awareness' on the S-DERS, in the hangover versus the no-hangover condition. Hangover did not impair emotion regulation ability as assessed using the lab-based task ( P s ≥ 0.21, d s ≤ 0.40), but there was a general negative shift in valence ratings (i.e. all images were rated more negatively) in the hangover relative to the no-hangover condition ( P < 0.001, d = 1.16). Conclusion: These results suggest that emotion regulation in everyday life and emotional reactivity may be adversely affected by alcohol hangover, but some emotion regulation strategies (e.g. deliberate cognitive reappraisal) may be unaffected.